2018
DOI: 10.1002/stem.2956
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Factors Released by Osteoblasts Provide Strong Platelet Engraftment Properties

Abstract: Ex vivo expansion of hematopoietic stem cell (HSCs) and progenitors may one day overcome the slow platelet engraftment kinetics associated with umbilical cord blood transplantation. Serumfree medium conditioned with osteoblasts (i.e., osteoblast-conditioned medium [OCM]) derived from mesenchymal stromal cells (MSC) was previously shown to increase cell growth and raise the levels of human platelets in mice transplanted with OCM-expanded progenitors. Herein, we characterized the cellular and molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…IGF-2 also acted as an important mitogen regarding liver repopulation in animal model [21]. IGF-2 was reported to be at higher level in the osteoblast-conditioned medium when compared with the control medium conditioned with the stem cells [22]. The expression of IGF-2 in developing osteophyte was strongly associated with a degree of osteogenesis, with the highest expression in active osteoblasts [23].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-2 also acted as an important mitogen regarding liver repopulation in animal model [21]. IGF-2 was reported to be at higher level in the osteoblast-conditioned medium when compared with the control medium conditioned with the stem cells [22]. The expression of IGF-2 in developing osteophyte was strongly associated with a degree of osteogenesis, with the highest expression in active osteoblasts [23].…”
Section: Discussionmentioning
confidence: 99%
“…While ex vivo expansion of HSC and progenitors is not currently feasible, it is an active area of research. In a recent article in Stem Cells , Abu‐Khader et al explore the mechanisms of action of MSC‐derived osteoblast conditioned media (OCM) to increase engraftment potential of ex vivo produced progenitor cells . They had previously shown that OCM could increase expansion and engraftment of UCB CD34+, and used these studies as a foundation to gain further understanding of the molecular mechanisms behind their findings .…”
Section: Featured Articlesmentioning
confidence: 99%
“…One method to enhance their therapeutic potential is by stimulating these responses before cell administration by some pretreatment strategy that is specific to the mechanism of healing. In our second featured article, Abu‐Khader et al used conditioned medium from MSC‐derived osteoblasts to pre‐condition umbilical cord blood progenitor cells for enhanced platelet engraftment after transplant . In a related article, Abreu et al pre‐treated MSC with bronchoalveolar lavage fluid or serum from a murine model of allergic asthma to promote MSC anti‐inflammatory properties .…”
mentioning
confidence: 99%
“…paracrine signaling | secretome | secretion dynamics | paracrine dynamics | cell-cell communication S ecreted diffusive molecular factors are critical for intercellular communication enabling complex multicellular behaviors (1)(2)(3). Not surprisingly, therefore, secretion of various ligands is highly controlled, frequently dynamic in nature, and, like other cellular phenotypes, dependent on the biological context (4,5).…”
mentioning
confidence: 99%
“…Surprisingly, these cells, like other adult stem cell types, do not appear to directly integrate into the damaged tissue, but rather rapidly and completely clear from the site of MI (myocardial infarction) (10,17,18). This paradoxical finding has led to an increasing speculation that transient paracrine signaling is the principal mechanism accounting for BMSC function (1), explaining the survival and rescue of target tissues, including the heart (16,18).…”
mentioning
confidence: 99%